2019
DOI: 10.5811/cpcem.2019.6.43514
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care Transperineal Ultrasound to Diagnose Abscess in the Emergency Department

Abstract: Perineal and rectal pain are common presentations in the emergency department (ED). In the majority of cases, clinical examination is sufficient to detect local anorectal pathologies. However, perianal and rectal abscesses and fistulas are often the primary concerns prompting diagnostic imaging in the ED. Currently, computed tomography is the preferred imaging modality. Recently, transperineal ultrasound has emerged as an optimal imaging modality for the diagnosis of perineal and perianal abscesses. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Many different imaging modalities have been tried in the past, out of which ultrasonography is the most convenient and readily available investigation. Trans-anal ultrasound is often difficult to tolerate by patients in an already existing painful condition, however transcutaneous perineal ultrasound can offer diagnostic advantage in superficially assessing location and loco-regional extent of collection specially in emergency cases [ 9 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many different imaging modalities have been tried in the past, out of which ultrasonography is the most convenient and readily available investigation. Trans-anal ultrasound is often difficult to tolerate by patients in an already existing painful condition, however transcutaneous perineal ultrasound can offer diagnostic advantage in superficially assessing location and loco-regional extent of collection specially in emergency cases [ 9 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of this technique are multiple, but the results are highly operator sensitive due to the complex anatomy of the involved region and the substantial variability in patient presentation and location of rectal abscesses. In recent review, sonography demonstrated high accuracy in the identification of perianal abscesses [20], but the available evidence is too scarce to make a recommendation.…”
Section: B -In Patients With a Suspected Anorectal Abscess What Are The Appropriate Imaging Investigations?mentioning
confidence: 99%